Portfolio Optimization with Entropy-CRITIC-IDDWS- PROMETHEE Model in BIST Retail Trade Sector - Çilek, Arif; Seyranlıoğlu, Onur (International Journal of Economics and Financial Issues, 2024)
This research aims to construct an ideal stock portfolio by using financial data from firms in the BIST Retail Trade Sector throughout the 2022-2023 timeframe. Entropy, CRITIC, IDDWS and PROMETHEE methodologies were used in the study. The criterion weights were determined using the approaches of Entropy, CRITIC, and IDDWS. The alternatives were ranked using the PROMETHEE method. According to the Entropy method, the most effective evaluation criterion on performance is the return on equity ratio in 2022 and the asset turnover ratio in 2023, according to the CRITIC method, the financing ratio in 2022 and the current ratio in 2023, according to the IDDWS method, the financing ratio in 2022 and the asset turnover ratio in 2023. It was concluded that there were 6 companies with values between 0 and +1 in the entire 2022-2023 period, there were 6 companies on the efficient frontier. These firms are CASA, SOKM, VAKKO, BIMAS, SUWEN and TKNSA. The study has a very unique perspective in terms of both proposing a new and original integrated model (Entropy-CRITIC-IDDWS-PROMETHEE) to investors about optimal portfolio selection and testing the proposed model for the 1st time in this study and the breadth of the data set used.